The workload of Indonesian nurses working in Saudi Arabia after COVID-19 pandemic: A phenomenological study - Akhir Fahruddin; Slametiningsih Slametiningsih; Nurul Uswatin; Ade Koswara (Journal of Holistic Nursing Science, 2023)
Studies showed the significant impact on nurses' clinical experience and how they face work challenges during COVID-19. This study explores Indonesian nurses' working experiences in Saudi Arabia during the post-COVID-19 pandemic. A qualitative design with a phenomenological approach was used in this study. The inclusion criteria were 10 Indonesian nurses working in the COVID-19 ward, registered nurses at the Saudi Commission for Health Specialties (SCFHS), and able to participate in this research, while the exclusion criteria were out of those criteria. A semi-structured interview was used in a suitable setting, and the data transcription followed seven steps of Colaizzi's analysis. Three themes were identified: burnout, support system, and job satisfaction. These themes reflect the workload of Indonesian nurses who work in the government hospital in Saudi Arabia. All participants were exhausted in the post-COVID-19 pandemic. The researcher recommended the need for comprehensive support by the government and suggested established policies that reduce the psychological problem of non-Saudi nurses in post-pandemic COVID-19. Keywords: COVID-19; Indonesian nurse; working experiences; phenomenological study; Saudi Arabia